Grit is associated with psychological health among older sexual minority men. (1st February 2023) - Okafor, Chukwuemeka N.; Brennan-Ing, Mark; Ware, Deanna; Haberlen, Sabina; Egan, James E.; Brown, Andre L.; Meanley, Steven; Stosor, Valentina; Shoptaw, Steven; Friedman, M. Reuel; Plankey, Michael
Abstract: Objectives: Studies have shown that grit—defined as perseverance and passion for achieving one's long-term goals—is associated with improved health outcomes, including lower levels of psychological distress. However, the psychometric properties of the original Grit Scale (Grit-O Scale) has not been validated among sexual minority men (SMM). The present study aimed to validate the Grit-O Scale among a sample of older SMM and assess the relationships between the Grit-O Scale factors and symptoms of psychological distress. Method: We used data from a single visit of participants in the Multicenter AIDS Cohort Study (MACS) Healthy Aging longitudinal study. The sample included 981 older SMM (mean age = 61, SD = 8.5) with and without HIV. We conducted confirmatory factor analysis (CFA) to identify the two factors of the Grit-O Scale: consistency of interest and perseverance of effort. We also conducted a latent profile analysis (LPA) to identify distinct profiles of psychological distress from self-reported scales of depression, anxiety, and perceived stress. Results: The Grit-O Scale showed acceptable reliability estimates for the items with Cronbach's alpha reliability coefficients ranging from 0.77 to 0.82. The CFA identified the two factors of the Grit-O Scale with acceptable model fit (root mean square error of approximation = 0.058 [95% CI = 0.050, 0.067], comparative fit index = 0.95, Tucker-Lewis Index = 0.93, standardized root mean square residual = 0.07). The LPA yielded three mutually exclusive profiles of psychological distress (profile 1: low stress, anxiety, and depression; profile 2: high stress and depression and low anxiety; and profile 3: high stress, anxiety, and depression). In adjusted multinominal logistic regression analysis, we found that both higher levels of consistency of interest and perseverance of effort factors of the Grit-O Scale were significantly associated with decreased odds of being in profiles 2 and 3 compared with being in profile 1. Conclusion: Our findings support the use of the Grit-O Scale among older SMM. Grit factors could explain variability in the negative psychological symptoms among older SMM and warrant further investigation. Supplemental data for this article is available online at http://dx.doi.org/10.1080/13607863.2022.2032594